EFL Students’ Perceptions of Reading for Pleasure in Indonesian Higher Education: Motivation, Habits, Material Preferences, and Language Skill Development - Dyah Kusumastuti; Aulia Dien, Athayazhafirah; Lowe, Katim (Script Journal: Journal of Linguistics and English Teaching, 2026)
Background:  This study explores the EFL university students’ perceptions of Reading for Pleasure (RfP) in terms of reading motivation, reading habits, material preferences, and perceived English language skill development.  Methodology:  A quantitative descriptive research design was employed. Data collected from 35 second semester students of English Education at one of the private universities in Central Java by using a validated questionnaire. Findings:  Results show that students have a high opinion of so-called RfP, especially its effect on vocabulary and reading comprehension (more than 80%). Much of the motivation is instrumental in nature, and students read to get better at reading rather than to enjoy it. The participation is still sporadic due to the time (71.4 %) and low institutional (42.9%) support for research. For media preference, the results show that materials of choice are fictional works (82.8%) and digital versions (74.3%), indicating change in reading habits. The findings of the regression analysis provide evidence that investment in reading as an activity has a greater effect on skill development (β = 1.50) than motivation, reinforcing the importance of turning motivation into practice over time. Conclusion:  Students acknowledged the linguistic and academic benefits of RfP. The school-level practices, including organized RfP activities, rich materials and an autonomy supportive climate are critical to cultivation of consistent reading habits and comprehensive language knowledge. Use of longitudinal designs and digital/collaborative reading practice might provide further explanation to sustaining engagement. Originality:  Despite the well-established influence, with evidence of its positive contributions on learners, few studies have addressed how motivation, reading habits, material preference and perceived skill development interrelate in Indonesian higher education.